Driving the Future: A Management Flight Simulator of the US Automobile Market. (December 2017) - Keith, David R.; Naumov, Sergey; Sterman, John
Background. A significant gap exists in the United States between ambitious regulatory goals requiring firms to introduce hybrid and electric vehicles, and consumer adoption of these technologies to date. However, the interventions required to close this gap are not obvious due to the complex feedbacks and time delays that governalternative fuel vehicle (AFV) diffusion . Purpose. The purpose of this article is to introduce Driving the Future (DtF), a free, web-basedmanagement flight simulator to explore the effects of automaker strategies and public policies on the US automotive market. Method. We develop a behavioral, dynamic model portraying multiple automobile and fuel types, fueling infrastructure, and consumer choices, enabling users to rapidly experiment with how a wide array of decisions and assumptions shape the dynamics of AFV diffusion out to 2050. Results. We describe how the simulator can be used to explore various scenarios for AFV adoption, and discuss how the simulator can help improve mental models and decision-making. We present evidence from classroom and online experiments, demonstrating that the simulation is both effective in developing users' understanding of AFV diffusion dynamics, and enjoyable to use.